Effects of carbohydrate ingestion on skill maintenance in squash players - Bottoms, L. M.; Hunter, A. M.; Galloway, S. D. R. (European Journal of Sport Science, 2006)
The effects of carbohydrate (CHO) ingestion during sports which require high levels of motor and cognitive skill, such as squash, have produced conflicting results. This study aimed to explore the effect of CHO ingestion on squash skill following short duration exercise simulating the demands of squash play. Sixteen male squash players of a high standard were recruited. Following a VO2max test, and familiarisation trial, subjects completed two further trials assessing skill pre- and post-exercise designed to simulate the demands of squash play. A squash skill test assessed accuracy of the forehand and backhand straight drives. Exercise consisted of 20 minutes of shuttle running at 82(±5)% HRmax, and 9 minutes of ghosting at 94(±4)% HRmax. Capillary blood samples (20 µl) were taken at five intervals for measurement of glucose and lactate. Cognitive function was measured with choice visual and auditory reaction time (RT) tests pre- and post-exercise, as was forearm wrist flexor MVC and fatigue profile. CHO drink (6.4% CHO) or matched placebo (PL) were administered after the initial skill test (500 ml), after the shuttle running (250 ml), and after the ghosting (250 ml) in a double blind crossover design. There was no overall effect of CHO ingestion on skill maintenance (p=0.10) however, significantly fewer balls landed outside the scoring zone (p=0.03) on the CHO ingestion trial. There was no change of visual RT pre- to post-exercise on PL (+0.01±0.03s), but a significant improvement (-0.07±0.05s) was observed in the CHO trial. Auditory RT improved pre- to post-exercise during both trials. MVC and fatigue profile of the wrist flexors was not different between trials but showed a force decrement pre- to post-exercise (p<0.05). A significant difference in blood glucose was observed between trials (p<0.01) but blood lactate response during both trials was similar. These results lend some support to a beneficial effect of CHO ingestion on skill during game sports.